Interconfessional Contacts and Conflicts in the Peloponnesos (Thirteenth to Fourteenth Century) - Belorussova, Tatiana Evgenievna (Antičnaâ drevnostʹ i srednie veka, 2023)
The purpose of this article is to analyze the features of interconfessional interaction of the Romaioi, Franks, and Venetians in the Peloponnesos in the thirteenth and fourteenth centuries, from the Latin invasion to the period when certain traditions of interconfessional communication between the conquerors and the Romaioi developed. Using the accounts of the Chronicle of the Moraia, resolutions of the Venetian Senate, Venetian private-law documents, as well as Byzantine historical (George Akropolites, George Pachymeres, John VI Kantakouzenos), polemical (John VI Kan- takouzenos), and epistolary (Gregory Akindynos) writings, the article has analyzed the features of Greek-Latin contacts in the religious sphere, the nature of the contra- dictions between the Orthodox and the Catholics, the cases of change of confession and combined worship, considering the incidence of the said phenomena. The con- clusion is that the gateway to the long-term and relatively peaceful coexistence of the Greeks and Latins in the Peloponnesos was the Latins’ loyal policy towards the other-believers performed from the moment they initially appeared on the peninsula. In case of the biggest part of the Greek-Latin population of the Moraia, their relations with neighbours were most often of a compromise nature. Peaceful forms of inter- confessional contacts between the Latins and the Romaioi were more common than open conflicts on religious grounds. The arousing conflicts were generally associated with the actions of specific figures of strangers who represented the central government, and often had a pronounced political colouring.